Mali : Sixth Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2003)
This report summarizes the sixth review of the economic program of Mali under the Poverty Reduction and Growth Facility (PRGF) and assesses the progress made in adjusting the economy. The Malian authorities continued to make good progress in implementing the IMF program, under difficult conditions. Executive Directors stressed the need for prudent macroeconomic policies and structural reforms. They emphasized the need to enhance private sector competitiveness, liberalize the cotton sector, and promote good governance.